We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
107
4
avatar+112 

Let x,y, and z be positive real numbers such that \(\frac{1}{x^4} + \frac{1}{y^4} + \frac{1}{z^4} = 1.\)
Find the minimum value of \(\frac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^3 y^2 z^3}.\)

 Oct 15, 2019
 #1
avatar+435 
+8

Look at this link it might help you?

 

https://web2.0calc.com/questions/1-let-x-y-and-z-be-real-numbers-such-that-find-the

 Oct 15, 2019
 #2
avatar
+1

x = 3^1/4,   y = 3^1/4,    z=3^1/4.

 

The minimum value of:  \frac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^3 y^2 z^3} = 3

 Oct 15, 2019
 #3
avatar+6045 
+1

....

Rom  Oct 16, 2019
edited by Rom  Oct 18, 2019
 #4
avatar+23324 
+3

Let x,y, and z be positive real numbers such that \(\dfrac{1}{x^4} + \dfrac{1}{y^4} + \dfrac{1}{z^4}\) = 1.
Find the minimum value of \(\dfrac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^3 y^2 z^3}\).

 

1.  \(x^4 y^4 + x^4 z^4 + y^4 z^4 = \ ?\)

\(\begin{array}{|rcll|} \hline \dfrac{1}{x^4} + \dfrac{1}{y^4} + \dfrac{1}{z^4} &=& \dfrac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^4 y^4 z^4} \\\\ 1 &=& \dfrac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^4 y^4 z^4} \\\\ \mathbf{x^4 y^4 + x^4 z^4 + y^4 z^4} &=& \mathbf{ x^4 y^4 z^4 } \\ \hline \end{array}\)

 

2. rearrange \(\dfrac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^3 y^2 z^3}\)

\(\begin{array}{|rcll|} \hline \dfrac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^3 y^2 z^3} &=& \dfrac{x^4 y^4 z^4 } {x^3 y^2 z^3} \\\\ \mathbf{\dfrac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^3 y^2 z^3} } &=& \mathbf{x y^2 z} \\ \hline \end{array}\)

 

Lagrange Multipliers

\(\begin{array}{|rcll|} \hline g(x,y,z) &=& \dfrac{1}{x^4} + \dfrac{1}{y^4} + \dfrac{1}{z^4} - 1 = 0 \\\\ f(x,y,z) &=& xy^2z \rightarrow \text{MIN.} \\\\ L(x,y,z,\lambda) &=& \underbrace{xy^2z}_{f(x,y,z)} + \lambda \left( \underbrace{\dfrac{1}{x^4} + \dfrac{1}{y^4} + \dfrac{1}{z^4} - 1 }_{g(x,y,z)}\right) \\\\ \hline \frac{\partial L(x,y,z,\lambda)}{\partial x} &=& y^2z-\dfrac{4}{x^5} \lambda \\\\ \frac{\partial L(x,y,z,\lambda)}{\partial y} &=& 2xyz-\dfrac{4}{y^5} \lambda \\\\ \frac{\partial L(x,y,z,\lambda)}{\partial z} &=& xy^2-\dfrac{4}{z^5} \lambda \\\\ \frac{\partial L(x,y,z,\lambda)}{\partial \lambda} &=& 0+ \dfrac{1}{x^4} + \dfrac{1}{y^4} + \dfrac{1}{z^4}-1 \\ \hline \end{array} \)

 

\(\begin{array}{|lrcll|} \hline & y^2z-\dfrac{4}{x^5} \lambda &=& 0 \quad | \quad \cdot x^5 \\\\ (1) & y^2x^5z-4\lambda &=& 0 \\ \hline & 2xyz-\dfrac{4}{y^5} \lambda &=& 0 \quad | \quad \cdot y^5 \\\\ (2) & 2xy^6z-4\lambda &=& 0 \\ \hline & xy^2-\dfrac{4}{z^5} \lambda &=& 0 \quad | \quad \cdot z^5 \\\\ (3) & xy^2z^5-4\lambda &=& 0 \\ \hline (4) & \dfrac{1}{x^4} + \dfrac{1}{y^4} + \dfrac{1}{z^4}-1 &=& 0 \\ \hline \end{array}\)

 

\(\begin{array}{|lrcll|} \hline & y^2x^5z-4\lambda &=& 0 \qquad (1) \\ (5) & \mathbf{z} &=& \mathbf{ \dfrac{4\lambda}{y^2x^5} } \\ \hline \hline & 2xy^6z-4\lambda &=& 0 \qquad (2) \\ (7) & \mathbf{x} &=& \mathbf{ \dfrac{4\lambda}{2y^6z} } \\ \hline & 2xy^6z-4\lambda &=& 0 \qquad (2) \quad | \quad \mathbf{z=\dfrac{4\lambda}{y^2x^5} } \\ & 2xy^6\dfrac{4\lambda}{y^2x^5}-4\lambda &=& 0 \\ & 2y^4\dfrac{4\lambda}{x^4} &=& 4\lambda \\ & 2y^4 &=& x^4 \\ (8)& \mathbf{y^4} &=& \mathbf{\dfrac{x^4}{2}} \\ \hline & xy^2z^5-4\lambda &=& 0 \qquad (3) \quad | \quad \mathbf{x=\dfrac{4\lambda}{2y^6z} } \\ & \dfrac{4\lambda}{2y^6z}y^2z^5-4\lambda &=& 0 \\ & \dfrac{4\lambda}{2y^4}z^4 &=& 4\lambda \\ & z^4 &=& 2y^4 \\ (9) & \mathbf{y^4} &=& \mathbf{ \dfrac{z^4}{2} } \\ \hline (8)=(9): & y^4 = \dfrac{x^4}{2} &=& \dfrac{z^4}{2} \\\\ (10) & \mathbf{x^4} &=& \mathbf{z^4} \\ \hline \end{array} \)

 

\(\mathbf{z=\ ?}\)

\(\begin{array}{|rcll|} \hline \dfrac{1}{x^4} + \dfrac{1}{y^4} + \dfrac{1}{z^4}-1 &=& 0 \qquad (4) \quad | \quad \mathbf{x^4=z^4} \\\\ \dfrac{1}{z^4} + \dfrac{1}{y^4} + \dfrac{1}{z^4}-1 &=& 0 \quad | \quad \mathbf{y^4=\dfrac{z^4}{2}} \\\\ \dfrac{1}{z^4} + \dfrac{1}{\dfrac{z^4}{2}} + \dfrac{1}{z^4}-1 &=& 0 \\\\ \dfrac{1}{z^4} + \dfrac{2}{z^4} + \dfrac{1}{z^4} &=& 1 \\\\ \dfrac{4}{z^4} &=& 1 \\\\ z^4 &=& 4 \\ z^2 &=& 2 \\ \mathbf{z} &=& \mathbf{\sqrt{2}} \\ \hline \end{array} \)

 

\(\mathbf{x=\ ?} \)

\(\begin{array}{|rcll|} \hline \mathbf{x^4} &=& \mathbf{z^4} \qquad (10) \quad | \quad \mathbf{z^4 = 4} \\\\ x^4 &=& 4 \\ x^2 &=& 2 \\ \mathbf{x} &=& \mathbf{\sqrt{2}} \\ \hline \end{array}\)

 

\(\mathbf{y=\ ?}\)

\(\begin{array}{|rcll|} \hline \mathbf{y^4} &=& \mathbf{\dfrac{z^4}{2} } \qquad (9) \quad | \quad \mathbf{z^4 = 4} \\ y^4 &=& \dfrac{4}{2} \\ y^4 &=& 2 \\ y &=& \sqrt[4]{2} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \mathbf{\dfrac{x^4 y^4 + x^4 z^4 + y^4 z^4}{x^3 y^2 z^3}} &=& xy^2z \\\\ &=& \sqrt{2} \left( \sqrt[4]{2} \right)^2 \sqrt{2} \\ &=& 2 \cdot \left( \sqrt[4]{2} \right)^2 \\ &=& 2\cdot 2^{\frac{2}{4}} \\ &=& 2\cdot 2^{\frac{1}{2}} \\ &=& \mathbf{2 \sqrt{2}} \\ \hline \end{array}\)

 

 

laugh

 Oct 17, 2019

17 Online Users

avatar
avatar
avatar